Perceptions and feelings of a French sample regarding lung cancer screening - Nicolas Darnaud; Jean-Eudes Mory; Pascal Romy; Jacques Berger; Karine Eve; Sophie Lantheaume (BMC, 2023)
Abstract Introduction This study investigated the perceptions and feelings of a French sample about the possible introduction of lung cancer screening. Methods A total of 146 individuals, aged between 19- and 64-years, participated in this study conducted between November 2020 and January 2021. Participants were divided into three groups according to their smoking status: (i) active smokers (G1); former smokers (G2); and non-smokers (G3). Each individual completed an online questionnaire evaluating their perceptions and feelings about lung cancer, screening and scans. Results Overall, a higher percentage of former smokers (47%) indicated a greater willingness to participate in lung cancer screening compared to active smokers (19%) and non-smokers (32%). Active smokers and former smokers reported anxiety about the development of lung cancer. Active smokers who wished to participate in screening reported a greater motivation to reduce their tobacco consumption. The perception of lung cancer risk had less influence than age and socio-economic category on the participation in screening. Finally, stigma did not appear to be a barrier to undergoing screening. Conclusion Active and former smokers were generally optimistic about screening; however, active smokers showed less inclination to participate in screening compared to former smokers and non-smokers. Three main factors appeared to influence this participation: the perception of the risk of developing cancer, age and socio-economic category.